THYROID CANCER AND SPECIAL FEATURE OF BACKGROUND THYROID PARENCHYMA (twenty-five year old study) - MuzhichukА.V.; Afanasyeva, N.I.; Muzhichuk, V.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Analysis of the clinical cases of thyroid cancer (TC) in 2506 patients, operated or treated in the Institute of medical radiology for the elongation 1982-2006 yr. was carried out. State of thyroid gland parenchyma, where malignant tumor was developed, was analyzed. Also, the morphological version of thyroid cancer was determined. The total quantity of the patients with TC, a quantity and the percentage of cancer, which flowed together with the benign thyroid gland pathology, correspondingly, a quantity and the percentage of the “clean” thyroid cancer was determined to. An increase of primary thyroid carcinomas for a twenty year period, which passed after Chernobyl accident was noted. The most intensive increase of TC is fixed for the last five year period – 2001-2006. In the high percentage of cases (16-47) tumor was developed against the background benign thyroid pathology, most frequently on the diverse variants of goiter and autoimmune thyroiditis. Last time a clear increase in the quantity of all versions of thyroid cancer, which appears against the background of the benign thyroid pathology is outlined.